Through a nutritional improvement project, Bogor District had donated powdered milk formula (PMF) for severe malnutrition children under five years. Powdered milk formula was assumed as an unsterilized product, because it might contain spore forming bacteria. To evaluate the bacterial contaminant of home prepared milk formula, fourty eight samples of PMF, and 50 samples of reconstitution formula, drinking water, drinking equipment, and hand were taken proporsionally from the mothers in 10 Heal - Maya Purwanti; Mirnawati Sudarwanto; Winiati P. Rahayu; A. Winny Sanjaya (Forum Pasca Sarjana, 2008)
Through a nutritional improvement project, Bogor District had donated powdered milk formula (PMF) for severe malnutrition children under five years. Powdered milk formula was assumed as an unsterilized product, because it might contain spore forming bacteria. To evaluate the bacterial contaminant of home prepared milk formula, fourty eight samples of PMF, and 50 samples of reconstitution formula, drinking water, drinking equipment, and hand were taken proporsionally from the mothers in 10 Health Community Centre around Bogor District. Samples were analyzed for aerobic microbe, Bacillus cereus, Clostridium perfringens, and the potential of enterotoxins production. All of the donated PMF samples exhibiting a total aerobic count of <104 CFU/g (mean 1.2 x 102 CFU/g) and B. cereus count of <103 CFU/g (mean 3.0 x 102 CFU/g for PMF containing this bacterium). Improper home storage promote the growth of aerobic microbe and B. cereus. Improper preparation promote the growth of B. cereus which present initially at low level (mean 7.8 x 10 CFU/g) and became 1.6 x 103 CFU/ml after the reconstitution. Clostridium perfringens emerge at 4 samples (mean 1.5 x 10 CFU/ml) after the reconstitution. Several isolate of B. cereus (4 from PMF, 13 from opened PMF, and 2 from reconstution formula) showed a possibility to produce diarrheagenic enterotoxin while the isolate of C. perfringens did not shown it. Keywords: powdered milk formula, B. cereus, C. perfringens, diarrheagenic enterotoxin, preparation and storage